2020
DOI: 10.37290/ctnr2641-452x.18:343-347
|View full text |Cite
|
Sign up to set email alerts
|

Consumers� Attitudes Toward Functional Foods: A�Review

Abstract: The market for functional foods, fortified with added nutrients such as minerals, vitamins, micronutrients, antioxidants and fibers, is on the rise. In this review, we discuss the concept and nature of functional foods, the constituents or ingredients that are commonly used to fortify these foods, and the purpose of fortification. Finally, the review surveys consumers� attitudes toward functional foods and their importance to help their development and marketing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…It should be added that the group most likely to consume probiotic supplements included mostly women. Many studies have shown that care for health is a distinctive feature of women, while men do not attach such importance to it [Babicz-Zielińska 2010; Kozirok, Baumgart and Babicz-Zielińska 2012; Czapiński and Panek 2015;Zabrocki and Suszek 2018;Bakshi, Chhabra and Kaur 2020]. At the same time it was shown that both gender and frequency of consumption of dietary supplements significantly differentiated consumer attitudes in these groups (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…It should be added that the group most likely to consume probiotic supplements included mostly women. Many studies have shown that care for health is a distinctive feature of women, while men do not attach such importance to it [Babicz-Zielińska 2010; Kozirok, Baumgart and Babicz-Zielińska 2012; Czapiński and Panek 2015;Zabrocki and Suszek 2018;Bakshi, Chhabra and Kaur 2020]. At the same time it was shown that both gender and frequency of consumption of dietary supplements significantly differentiated consumer attitudes in these groups (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Studying the connections between these two very important tradicional healing gifts of nature is a great challenge and also the focus of many studies (Yamani, 2015). Research and innovation in the formulation of new food products, belonging to a functional food group, are steadily increasing (Bigliardi and Galati, 2013;Birch and Bonwick, 2019;Bakshi et al, 2020;Colombo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A number of surveys have indicated that many consumers will pay a premium price for functional foods demonstrated to contain high levels of such health-benefiting compounds [9][10][11][12]. Several recent reviews have been published outlining the definition, diversity and consumer awareness of functional foods; the interested reader is referred to these publications for more details [13][14][15][16][17]. However, there is a general lack of knowledge around functional food in the Australian horticulture & fresh produce sector.…”
Section: Introductionmentioning
confidence: 99%